The learning styles of the special needs children using pictures and storyboard writing: A case study / Normaliza Abd. Rahim and Nik Ismail Harun - Abd. Rahim, Normaliza; Harun, Nik Ismail (Universiti Teknologi MARA Cawangan Pahang, 2007)
This study explores the learning styles of three special needs children at Lynncroft Primary School, Nottingham. A one year study with a group of 12 children with different abilities and needs was carried out with the help of 3 teacher assistants. One of the researchers who was also the teacher in the classroom carried out the normal teaching and learning with the children by using pictures and ICT in the classroom. The pictures involved were taken by the children. The use of digital camera was introduced for the purpose of this study. After the pictures were taken and downloaded in the computer, the children would try to arrange the pictures accordingly to make a storyline. The children would, then, type their story in the computer. Activities were differentiated for all the children in the classroom. The three children were picked based on their abilities and special needs. This study has given a big contribution towards the school especially for the future special needs teacher.